TEALS - Elias, Jaan; Cooney, Kate; Rosenthal, Jean (London : Yale School of Management, 2020)
In 2019, TEALS (Technology Education And Literacy in Schools), a program built to pair software engineers with high schools to develop computer literacy, faced a crossroads. Should it stay under the Microsoft philanthropic umbrella or venture out on their own?
Originally Published InElias, J., Rosenthal, J., & Cooney, K. (2020). TEALS. 19-024. New Haven, CT: Yale School of Management, Yale University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Decision making; Small business -- Growth